Usborne illustrated stories of horses & ponies - Dickins, Rosie; Davidson, Susanna Patchett, Fiona Hore, Rosie Daynes, Katie (Usborne Publishing London, 2017)
Meet magical flying horses, brave royal steeds and clever little ponies in this illustrated collection of myths and fairytales